2022
DOI: 10.1111/febs.16442
|View full text |Cite
|
Sign up to set email alerts
|

A recent update on small‐molecule kinase inhibitors for targeted cancer therapy and their therapeutic insights from mass spectrometry‐based proteomic analysis

Abstract: Kinases are key regulatory signalling proteins governing numerous essential biological processes and cellular functions. Dysregulation of many protein kinases is associated with cancer initiation and progression. Given their crucial roles, there has been increasing interest in harnessing kinases as prospective drug targets for cancer. In recent decades, numerous small‐molecule kinase inhibitors have been developed and revolutionized the cancer treatment landscape. Despite their great potential, challenges rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 107 publications
0
28
0
Order By: Relevance
“…From 2011 to 2013, total of 14 kinase inhibitor drugs were approved by the FDA for various types of cancers. Since 1999, around 70 drugs got approval from FDA till Dec 2021 and still many more drugs are under clinical trial for many new kinase in hibitors [25,91,92].…”
Section: Fda Approved Drugs As Targetsmentioning
confidence: 99%
“…From 2011 to 2013, total of 14 kinase inhibitor drugs were approved by the FDA for various types of cancers. Since 1999, around 70 drugs got approval from FDA till Dec 2021 and still many more drugs are under clinical trial for many new kinase in hibitors [25,91,92].…”
Section: Fda Approved Drugs As Targetsmentioning
confidence: 99%
“…MEK1/2 inhibitors, which bind at a particular cavity close to the ATP-binding site, are some of the well-studied type III inhibitors. Trametinib, Selumetinib, Binimetinib, and Cobimetinib are allosteric inhibitors of MEK and are among the MEK inhibitors currently approved by the FDA [38,[53][54][55][56]. The regions outside the ATP-binding sites are the focus of Type IV inhibitors, also known as substrate-directed inhibitors, which are allosteric inhibitors that do not overlap with Type III inhibitors.…”
Section: Targets For Developing Kinase Inhibitorsmentioning
confidence: 99%
“…These are less potent than other types of inhibitors and do not directly prevent binding at the kinase domain/ligand-polypeptide binding site. SSR128129E and WRG-28 are two examples of this type of kinase inhibitor, which inhibits the FGFR (extracellular domain of fibroblast growth factor receptor) family and DDRs (discoidin domain receptors), respectively [7,41,53,56,57]. The structured kinase mapping analyses revealed that approximately 200 kinases have wide-open cysteine available at the active sites, which could use in covalent inhibition [57].…”
Section: Targets For Developing Kinase Inhibitorsmentioning
confidence: 99%
“…Fusion genes are used as the targets of the therapeutics of cancer patients. Speci cally, kinase inhibitors are the most frequently treated drugs for driver fusion gene-positive patients (1,2). There are diverse working mechanisms of human fusion proteins that are awaiting to be targeted by the drugs (3).…”
Section: Introductionmentioning
confidence: 99%